Biosynthesis of Silver Nanoparticles Using Culture Supernatant of Shewanella sp. ARY1 and Their Antibacterial Activity - Mondal AH (Dove Medical Press, 2020)
Aftab Hossain Mondal,1,* Dhananjay Yadav,2,* Sayani Mitra,1 Kasturi Mukhopadhyay1 1Antimicrobial Research Laboratory, School of Environmental Sciences, Jawaharlal Nehru University, New Delhi 110067, India; 2Department of Medical Biotechnology, Yeungnam University, Gyeongsan 712-749, South Korea*These authors contributed equally to this workCorrespondence: Kasturi MukhopadhyaySchool of Environmental Sciences, Jawaharlal Nehru University, New Delhi 110067, IndiaTel +91 11-26704307Email kasturim@mail.jnu.ac.inPurpose: In this study, silver nanoparticles (AgNPs) were biosynthesized using culture supernatant of strain Shewanella sp. ARY1, characterized and their antibacterial activity was investigated against Gram-negative bacteria Escherichia coli and Klebsiella pneumoniae.Methods: The strain Shewanella sp. ARY1 was isolated from river Yamuna, Delhi and used for biosynthesis of AgNPs via extracellular approach. Biosynthesized AgNPs were characterized by UV-Visible (UV-Vis) spectrophotometer, fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), energy dispersive X-ray (EDX), transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Antibacterial activity of AgNPs was determined by well diffusion, broth microdilution and streaking plate assay to determine the zone of inhibition (ZOI), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), respectively. The effect of AgNPs on treated bacteria was investigated by electron microscopy analysis. Further, the biocompatibility of AgNPs was tested against mice erythrocytes (RBC) by hemolytic assay.Results: The UV-Vis spectral analysis revealed absorption maxima at 450 nm which confirmed the formation of AgNPs. The FTIR analysis suggested the involvement of various supernatant biomolecules, as reducing and capping agents in the synthesis of AgNPs. The XRD and EDX analysis confirmed the crystalline and metallic nature of AgNPs, respectively. The TEM and SEM analysis showed nanoparticles were spherical with an average size of 38 nm. The biosynthesized AgNPs inhibited the growth and formed a clear zone of inhibition (ZOI) against tested Gram-negative strains. The MIC and MBC were determined as 8-16 μg/mL and 32 μg/mL, respectively. Further, electron microscopy analysis of treated cells showed that AgNPs can damage the outer membrane, release of cytoplasmic contents, and alter the normal morphology of Gram-negative bacteria, leading to cell death. The hemolytic assay indicated that the biosynthesized AgNPs were biocompatible at low dose concentrations.Conclusion: This study demonstrates an eco-friendly process for extracellular synthesis of AgNPs using Shewanella sp. ARY1 and these AgNPs exhibited excellent antibacterial activity, which may be used to combat Gram-negative pathogens.Keywords: extracellular synthesis, eco-friendly process, AgNPs, antibacterial, Gram-negative bacteria, hemolytic activity